2022
DOI: 10.15586/aei.v50i2.550
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin ameliorates sepsis-induced lung capillary leak through inhibiting the JAK/STAT3 pathway

Abstract: Background: As a systemic inflammatory reaction, sepsis is associated with various organ dysfunctions. The capillary leakage and the imbalance between T helper 17 and regulatory T (Th17/Treg) cells are associated with sepsis-induced lung injury. Taxifolin (TXL) has been found to play a vital role in regulating this diverse disease. However, the detailed functioning and mechanism of TXL in regulating sepsis-induced lung capillary leak remain elusive. Methods: Balb/c mice were used to establish sepsis-induced lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…CD4 + T cell dysfunction plays a crucial role in humoral and cellular immune responses in sepsis [ 34 ]. It has also been demonstrated that abnormal Th17 cell is involved in sepsis-associated acute kidney injury, lung capillary leak, intestinal injury and lung injury [ [35] , [36] , [37] , [38] ]. Interleukin-17 (IL-17) is secreted by the Th17 subset of CD4 + T cell, which exerts potent pro-inflammatory effects [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cell dysfunction plays a crucial role in humoral and cellular immune responses in sepsis [ 34 ]. It has also been demonstrated that abnormal Th17 cell is involved in sepsis-associated acute kidney injury, lung capillary leak, intestinal injury and lung injury [ [35] , [36] , [37] , [38] ]. Interleukin-17 (IL-17) is secreted by the Th17 subset of CD4 + T cell, which exerts potent pro-inflammatory effects [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Janus kinase 2 signal transducer/transcription activator 3 (JAK2/STAT3) signaling pathway regulates inflammatory mediators involved in extracellular signaling pathways and plays an overall regulatory role in inflammatory responses and cell survival [19]. Most importantly, the JAK2/STAT3 signaling pathway is also involved in the regulation of Th17/Treg homeostasis [20]. In T lymphocytes, activated STAT3 mediates its downstream signaling pathway to enhance RORγt expression in initial CD4 + T lymphocytes, thereby contributing to the differentiation of CD4 + T cells to Th17 [21].…”
Section: Thementioning
confidence: 99%
“…[3][4][5] Traditional Chinese medicine has shown to have potent pharmacological functions in the treatment of lung diseases. 6 Rosavin, an alkyl benzene disaccharide, is one of the most crucial active components of Rhodiola, 7 which has been reported to have antidepressant, 8 anticancerous, 9 and antioxidant 10 effects. Recently, several studies have shown that Rosavin inhibits RANKL-induced osteoclast formation and suppresses inflammatory responses, thereby inhibiting bone loss.…”
Section: Introductionmentioning
confidence: 99%